EXAMINATION IN AUDITING. - Meigs, Walter B. (The Accounting Review, 1964)
The article presents solutions to questions that appeared in the November 7, 1963 Uniform Certified Public examination. There were in all 7 questions related to auditing. One question is related to the examination of fire insurance policies of the Cap Sales Company. Another question aims at opinions expressed by a Certified Public Accountant (CPA) on a client's financial statements. The third question asks for the discussion of control procedures for The United Charities organization based on its statement of receipts and disbursements. The fourth question relates to listing and discussion of various aspects of internal control by CPA after the examination of existing internal control of his client. The fifth question is related to audit procedures to be followed by a CPA in order to obtain an inventory certificate for a manufacturing company. The sixth question asks for information required by a CPA in order to audit a medium sized company's financial statements. The last question relates to preparation of auditor's adjusting journal entries for The Smoky Mountain Manufacturing Company.